PROYEKSI STOKASTIK PRODUKSI KEDELAI DI INDONESIA - Yurlia Pitasari; Agus Hudoyo; Achdiansyah Soelaiman (Lampung University, 2018)
Soybean is one of vegetable protein sources. It is so important that the government targets self-sufficiency on this commodity. Its target is 3.00 million tons in 2019, i.e. more than three times of the production in 2015. A production target is better stochastically forecasted that its result is an interval at a certain probability level. There were some studies that forecasted productions of soybean. However, their results were not as the intervals. Therefore, the objective of this research is for stochastically forecasting the soybean production. Its data are time series data obtained from the FAO and the Indonesian Statistics Central Bureau. Data were analyzed by using econometrics. The result of forecasting is the soybean production will be 0.99 million tons in 2019 with the 95% confidence interval between 0.94 and 1.05 million tons.Key words: Soybean, production, forecast